Análisis del tiempo de vida de las empresas familiares del sector calzado para damas en el distrito de Puente Piedra - 2015 - Alvarado Casallo, Chanel Patricio (2018)
This research work is based on the importance of carrying out an analysis on the causes of the problems in Lima family businesses in the women's footwear sector due to poor management of their resources, and the possible tools to solve said problems. conflicts Many of the big companies started as family initiatives to become the successful emporiums that they are today. For this reason, it is so important to know about the dynamics, strengths and weaknesses of these companies by including the affective element that characterizes them, although it also makes them vulnerable and perishable. The research was based on the study and interpretation of results obtained from interviews applied to managers of family businesses in the footwear sector for ladies in the Puente Piedra district, in order to appreciate aspects of succession and planning for the future. Among the problems of family businesses related to the sector that is being investigated, is because of nonformal, dysfunctional family organizations, demotivation, lack of commitment to the company, and problems related to succession (taxes, selection of leader ,and change resistance). The most appropriate method to reduce the inconveniences of the institutions or family businesses of the footwear sector, give importance to the human factor, in organizations and try to adapt the functions and responsibilities of the workers. The lack of a strategic plan has led to many family businesses to failure, so having one is recommended. Among the main reasons for the failure of family businesses is that they come to fill the position of a manager their children who do not have the capacity to assume such responsibility. And therefore generate conflicts in the family and in all its environment.